ANALYSIS OF FACTORS THAT INFLUENCE THE PAYMENT OF DEVIDENTS ON MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2012-2018 - Devi, Awaliani Praditya Karisma; Wijanti, Anita; Samrotun, Yuli Chomsatu (STIE Kusuma Negara, 2020)
This study aims to analyze free cash flow, net profit margins, debt to equity ratio, and company size on dividend payments. The sampling technique used purposive sampling. The research instrument was in the form of documentation of financial statements of banking companies listed on the Indonesia Stock Exchange (BEI) during the 2012-2018 period. The samples used were 5 companies with a total of 21 samples over a period of 7 consecutive years of observation. The analysis technique used in this study is multiple linear regression assisted by SPSS version 22. Based on the results of the t test study, it shows that company size affects dividend payments and free cash flow, net profit margins, debt to equity ratio has no effect on dividend payments.